The All-Ukrainian Student Olympiad in “Statistics” Discipline: History, Results and Prospects - Momotiuk, L. Ye.; Gerasymenko, S. S.; Holubova, H. V. (Statistics of Ukraine, 2019)
The article is devoted to the analysis of results of the All-Ukrainian Student Olympiad in “Statistics” Discipline (referred hereafter as Olympiad) held in the National Academy of Statistics, Accounting and Audit (NASAA) in 2019. Given that NSAA Olympiad in statistics has been organized since 2012, the authors analyze change in the geographical structure of Olympiad participants in the period under study. Olympiad – 2019 engaged 46 participants from 21 Ukrainian HEEs. The largest share of participants comes from northern regions of Ukraine (52.2%), which is 26.7 percentage points higher than in 2012; nearly one of the four participants (23.9%) is from the Central Ukraine and 17.4% – from the Western Ukraine, with the latter two shares being almost unchanged, and 6.5% come from the East of Ukraine, which is 4.4 percentage points lower than in 2012. Of the HEEs located in Eastern regions of Ukraine, only Donetsk National University was represented, accommodated temporarily in the city of Vinnytsia and, therefore, counted in the Central region by geographic locality. The largest number of Olympiad participants was in 2013 (85 students), with nearly 25% of participants coming from Eastern regions of Ukraine, and Olympiad events arranged as part of international collaboration with the Russian Federation. It was 8 Russian students that came to Ukraine that time: three from Moscow State University of Economics, Statistics and Informatics; three from Saint-Petersburg State Economic University, and two from Transbaikal State University. The study reveals that 56 students from 16 Ukrainian HEEs were awarded over eight years of the All-Ukrainian Student Olympiad in “Statistics” Discipline. The leadership is with Kyiv National Taras Shevchenko University (15 awards or 26.8% of the total), nearly 18% of awards was received by students of NASAA, 12,5% – by students of Dnipropetrovsk Oles Honchar National University, 7% – Kyiv National Economic University named after Vadym Hetman, and 7% – Sumy State University. The analysis of mistakes made by Olympiad participants in 2019 shows that the most frequent ones occurred in the thematic sections: “Correlation analysis” and “Forecasting”. However, as the Olympiad participants used creative approaches to problem solution and demonstrated the mature statistical thinking they could be considered as professionally qualified. The authors gave firm arguments supporting the All-Ukrainian Student Olympiad in “Statistics” Discipline: it is useful for popularization of statistical literacy among the youth and fostering logical and unconventional thinking, promotion of their professional and intellectual development etc.